Experimental Study on the Effects of Refrigerant Inlet and Outlet Flow Directions on the Throttling Noise of Electronic Expansion Valve in Multisplit Heat Pump Air Conditioners - Zhu Tianjie; Zhan Feilong; Zhou Shaohua; Ding Guoliang; Cui Guodong; Diao Hongfu; Wang Haisheng (Zhileng xuebao, 2024)
The electronic expansion valve (EEV) used in multisplit heat pump air conditioners has the structural characteristics of import and export tubes perpendicular to each other, such that the refrigerant has two forms of flow into the EEV, that is, in the direction perpendicular to the valve needle axis and the direction parallel to the valve needle axis. The sound pressure level of the throttling noise exhibits evident differences in these two directions, and it is necessary to clarify the impact of the flow direction on the throttling noise. The purpose of this study is to design and build an experimental rig that can regulate the refrigerant state flowing into and out of the valve, observe the refrigerant flow pattern, and measure the sound pressure level of the throttling noise, thus obtaining the effects of the refrigerant flow directions on the throttling noise under different refrigerant flow rates and vapor qualities. The results show that when the refrigerant flows from the inlet pipe parallel to the direction of the valve needle axis, the throttling noise is mainly the collapse noise of vapor bubbles generated by the refrigerant throttling cavitation, and the overall noise sound pressure level is low. When the refrigerant flows from the inlet pipe perpendicular to the direction of the valve needle axis, the throttling noise is a combination of the noise due to bubble collapse and the noise due to vibrations of the valve needle, and the overall noise sound pressure level is high. In this experiment, the sound pressure levels of the throttling noise in these two flow directions range from 47.1 to 57.1 dB and 61.9 to 67.7 dB, respectively. The throttling noise in the air-conditioning system can be effectively reduced by optimizing the design of the refrigerant flow direction of the air-conditioning system and ensuring that the refrigerant always flows into the EEV from the inlet pipe parallel to the direction of the valve needle axis.